PsycEXTRA Dataset 2007
DOI: 10.1037/e527342012-554
|View full text |Cite
|
Sign up to set email alerts
|

Cue Effects on Memory for Location When Navigating Spatial Displays

Abstract: Participants maneuvered a rat image through a circular region on the computer screen to find a hidden target platform, blending aspects of two well-known spatial tasks. Like the Morris water maze task, participants first experienced a series of learning trials before having to navigate to the hidden target platform from different locations and orientations. Like the dot-location task, they determined the location of a position within a two-dimensional circular region. This procedure provided a way to examine h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 12 publications
(22 reference statements)
0
5
0
Order By: Relevance
“…The third experiment was a similar, but simplified, version of the task completed in Experiments 1 and 2. Experiment 3 blended the procedures used by Nardini et al (2008), Sjolund (2014), and Experiments 1 and 2, with the dot-replacement procedures used in the category prototype literature (Fitting et al, 2007;Fitting et al, 2009;Huttenlocher et al, 1991). First, instead of navigating through a three-dimensional virtual environment, participants were asked to remember the location of a target in a two-dimensional environment with a three-sided rectangle and a blue triangle as cues to location ( Figure 13).…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The third experiment was a similar, but simplified, version of the task completed in Experiments 1 and 2. Experiment 3 blended the procedures used by Nardini et al (2008), Sjolund (2014), and Experiments 1 and 2, with the dot-replacement procedures used in the category prototype literature (Fitting et al, 2007;Fitting et al, 2009;Huttenlocher et al, 1991). First, instead of navigating through a three-dimensional virtual environment, participants were asked to remember the location of a target in a two-dimensional environment with a three-sided rectangle and a blue triangle as cues to location ( Figure 13).…”
Section: Methodsmentioning
confidence: 99%
“…After four learning trials, 16 test trials measured navigation performance to the target location. Fitting et al (2009) found that navigation performance improved as the number of landmark cues increased. This suggests that participants were able to use multiple landmark cues together to improve memory for the goal location.…”
Section: Chapter 4 Experimentsmentioning
confidence: 99%
See 3 more Smart Citations